A Case of Hodgkin Lymphoma in a Patient with a History of Bone Pain and an Initial Diagnosis of Chronic Osteomyelitis. Issue 3 (May 2015) - Griguolo, Gaia; Mazzucchelli, Luca; Cavalli, Franco; Ceriani, Luca; Zucca, Emanuele; Stathis, Anastasios
Hodgkin lymphoma (HL) is an uncommon monoclonal lymphoid malignancy consisting of 2 main entities: classical HL and nodular lymphocyte predominant. Hodgkin lymphoma usually presents with peripheral lymphadenopathies, while extranodal involvement is rare. Prevalent osseous presentation is rare and still misdiagnosed, despite improvements in diagnostic techniques. Here we report the case of a 30-year-old man with multifocal HL bone involvement initially misdiagnosed as chronic recurrent osteomyelitis. This case emphasizes the difficulties in the diagnosis of HL presenting with bone pain and with radiologic skeletal findings not specific for lymphoma. These patients often have diagnostic delays and misdiagnosis. Repeated investigations and clinical suspicion of unusual presentations may be helpful in order to establish a correct diagnosis and start an effective treatment in this highly curable disease.